Analysis of the Central Nervous System Transcriptome of the Eastern Rock Lobster Sagmariasus verreauxi Reveals Its Putative Neuropeptidome - Ventura, Tomer (Public Library of Science, 2014)
Neuropeptides have been discovered in many arthropod species including crustaceans. The nature of their biological function is well studied and varies from behavior modulation to physiological regulation of complex biochemical processes such as metabolism, molt and reproduction. Due to their key role in these fundamental processes, neuropeptides are often targeted for modulating these processes to align with market demands in commercially important species. We generated a comprehensive transcriptome of the eyestalk and brain of one of the few commercially important spiny lobster species in the southern Hemisphere, the Eastern rock lobster Sagmariasus verreauxi and mined it for novel neuropeptide and protein hormone-encoding transcripts. We then characterized the predicted mature hormones to verify their validity based on conserved motifs and features known from previously reported hormones. Overall, 37 transcripts which are predicted to encode mature full-length/partial peptides/proteins were identified, representing 21 peptide/protein families/subfamilies. All transcripts had high similarity to hormones that were previously characterized in other decapod crustacean species or, where absent in crustaceans, in other arthropod species. These included, in addition to other proteins previously described in crustaceans, prohormone-3 and prohormone-4 which were previously identified only in insects. A homolog of the crustacean female sex hormone (CFSH), recently found to be female-specific in brachyuran crabs was found to have the same levels of expression in both male and female eyestalks, suggesting that the CFSH female specificity is not conserved throughout decapod crustaceans. Digital gene expression showed that 24 out of the 37 transcripts presented in this study have significant changes in expression between eyestalk and brain. In some cases a trend of difference between males and females could be seen. Taken together, this study provides a comprehensive neuropeptidome of a commercially important crustacean species with novel peptides and protein hormones identified for the first time in decapods.